The time course of spatial attention during naturalistic visual search. (January 2020) - Battistoni, Elisa; Kaiser, Daniel; Hickey, Clayton; Peelen, Marius V.
Abstract: In daily life, attention is often directed to high-level object attributes, such as when we look out for cars before crossing a road. Previous work used MEG decoding to investigate the influence of such category-based attention on the time course of object category representations. Attended object categories were more strongly represented than unattended categories from 180 msec after scene onset. In the present study, we used a similar approach to determine when attention is spatially focused on the target. Participants completed two tasks. In the first, they detected cars and people at varying locations in photographs of real-world scenes. In the second, they detected a cross that appeared at salient locations in an array of lines. Multivariate classifiers were trained on data of the artificial salience experiment and tested on data of the naturalistic visual search experiment. Results showed that the location of both target and distracter objects could be accurately decoded shortly after scene onset (50 msec). However, the emergence of spatial attentional selection – reflected in better decoding of target location than distracter location – emerged only later in time (240 msec). Target presence itself (irrespective of location and category) could be decoded from 180 msec after stimulus onset. Combined with earlier work, these results suggest that naturalistic category search operates through an initial spatially-global modulation of category processing that then guides attention to the location of the target.